Production of Dynamic Thermal Insulators By Coaxial Electrospinning of PAN and PEG - Boz, Ezgi Ceren; Önder Karaoğlu, Emel; SARIER, NİHAL; ARAT, REFİK (My University, 2015)
In the present work, we produced bicomponent nanofibers, composed of polyacrylonitrile (PAN) shells and PEG cores (PEG2000 and PEG4000), by co-axial electrospinning as new thermal energy storage materials that are suitable for further industrial uses. SEM images showed that the nanowebs of PAN-PEG shell-core nanofibers with smooth surfaces and of the average diameters smaller than 460 nm were successfully produced. The heat absorbed by PAN-PEG2000 nanoweb is 100.3 J/g between 50.6-56.5 C and of PAN-PEG4000 is 144.6 J/g between 54.0-60.7 C, which are quite remarkable in terms of their contribution to the dynamic thermal management of various textile products.